DRIVING FACTORS TO SELF-MARGINALITY BY IDENTITY EROSION WITHIN ROMANIAN GEOGRAPHICAL HIGHER EDUCATION - Alexandru GAVRIȘ (Revista Română de Geografie Politică)
The landscape of Geography within Romanian Higher Education might be at a crossroad. This is due to the over-focus on scientometric evaluations and the lack of tradition coupled to international research. In this context, we aim to highlight the role of Romanian geographers in the decline of their societal relevance, which is partly driven by an erosion of their internal identity. We identify the key factors contributing to Geography's marginalization within the Romanian academic framework and societal interests. Our analysis reveals a fragmentation of Geography as a discipline and scientific field, driven by centrifugal forces and a neglect of its foundational practices as parts of political influences.